Effect of annealing parameters on optoelectronic properties of highly ordered ZnO thin films. (September 2019) - Malik, Gaurav; Mourya, Satyendra; Jaiswal, Jyoti; Chandra, Ramesh
Abstract: In the present work, tuning in optoelectronic properties of sputter deposited zinc oxide (ZnO) thin films on ITO coated glass substrate have been investigated as a function of annealing parameters. Although, the annealing treatment is needed to tune the optoelectronic properties of ZnO layer but it can also modify the electrical properties a drastic change in sheet resistance (13 Ω/sq. to 23 ohm/sq.) was observed at an annealing temperature of 200 °C of underlying ITO substrate, which restricted maximum annealing temperature to 200 °C for ZnO at ITO. Vertically standing array of ZnO nano-pipes having single crystal orientation (002) with hexagonal structure, large crystallite size (∼24 nm), lowest lattice strain (0.621%), highest surface roughness (∼16 nm), and lowest R sh (12.3 KΩ/sq.) were obtained for sample annealed at 200 °C for 60 min. The XPS study also revealed that the sample annealed at 200 °C for 60 min contains lowest oxygen related vacancy (23.7), which favors the facile electrons transport when ZnO is used as an electron transport layer (ETL). SE and UV–Vis results revealed best optical parameters i.e., highest transmittance ( T ∼ 89%), refractive index ( n = 1.98 at 480 nm), and band gap ( E g = 3.30 eV), for the sample annealed at 200 °C for 60 min. These results indicated that ZnO nano-pipes based ETL may be a promising candidate for low temperature, high mobility, and cost-effective optoelectronic devices.